High-temperature electrolyte for a negative-electrode-free sodium-ion battery

CN123018133APending Publication Date: 2026-10-30ZHEJIANG ZHIYUAN NAKE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611481173.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但目前商用及常规醚类电解液多采用普通线性链状醚结构,存在明显技术短板:常规链状醚分子缺乏空间位阻保护,α氢活性较高,充放电过程中易发生还原裂解,引发电芯产气副反应;同时溶剂分子对钠离子溶剂化作用过强,高压工况下易在层状氧化物正极界面发生氧化分解,造成正极CEI膜破损、过渡金属溶出;此外,常规醚体系难以调控钠离子沉积均匀性,极易诱发钠枝晶生长,刺穿隔膜引发电池微短路,尤其在高温循环工况下,存在SEI膜易溶解、界面副反应加剧、容量快速衰减等问题,严重制约无负极钠离子电池的高温稳定性与长循环寿命

Benefits of technology

(1)本申请的一种用于无负极钠离子电池的高温电解液,采用非对称支链醚-吡咯烷类离子液体复配溶剂体系,搭配闭式笼型十二氢十二硼酸钠(Na2B12H12)作为添加剂,闭式笼型B12H122-阴离子骨架电子高度离域,对比NaBH4等简单硼氢盐,兼具优异的氧化与还原稳定性;离子液体改善添加剂在醚类溶剂中的溶解能力,非对称支链醚依靠分子特殊取代结构实现弱溶剂化效应、保护醚α氢,三者协同调控钠离子溶剂化鞘层,同时在正、负双侧电极界面构筑稳定的含硼无机组分钝化膜,改善电极-电解液界面特性,拓宽电解液电化学窗口,从根源上缓解无负极钠离子电池高温 SEI 膜溶解、高温产气、钠枝晶生长、高压下界面副反应加剧的技术难题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The application discloses a high-temperature electrolyte for a negative-electrode-free sodium ion battery, and belongs to the technical field of sodium ion batteries. 12 H 12 After the sodium salt, the additive and the solvent are mixed, the electrolyte for the negative-electrode-free sodium ion battery is obtained; the application adopts a compounded solvent system of the asymmetric branched ether-pyrrolidine ionic liquid, and is matched with Na2B 12 H 12 As the additive, the three synergistically control the sodium ion solvation sheath, and simultaneously construct a stable inorganic component passivation film containing boron on the interface of the positive electrode and the negative electrode, improve the electrode-electrolyte interface characteristics, widen the electrochemical window of the electrolyte, and fundamentally relieve the technical difficulties of the high-temperature SEI film dissolution, high-temperature gas production, sodium dendrite growth and intensified interface side reaction under high pressure of the negative-electrode-free sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of sodium-ion battery technology, and particularly relates to a high-temperature electrolyte for a negative electrode-free sodium-ion battery. Background Technology

[0002] Electrodeless sodium-ion batteries abandon traditional sodium-embedded anode materials. The battery does not pre-load metallic sodium; during charging, sodium ions are directly electroplated onto the surface of the negative electrode current collector, and sodium is stripped off during discharge. This simplifies the cell structure, reduces material costs, and significantly improves the battery's energy density, representing an important technological development path for high-energy-density sodium-ion batteries. The cycle life and operational safety of electrodeless sodium-ion batteries are highly dependent on the electrolyte system. On one hand, the electrolyte needs to precisely control the deposition behavior of sodium ions to achieve uniform, dendrite-free sodium electroplating / stripping on the current collector surface. On the other hand, the electrolyte needs to construct a highly stable passivation interface film on both the positive and negative electrode surfaces to suppress continuous solvent decomposition, high-temperature interface film dissolution, and cell gas generation, significantly reducing the irreversible consumption of active sodium.

[0003] Ether electrolytes are the mainstream solvent system for anode-less sodium-ion batteries due to their high ionic conductivity, moderate viscosity, and excellent stability against sodium reduction. However, most commercial and conventional ether electrolytes currently use ordinary linear chain ether structures, which have significant technical shortcomings: conventional chain ether molecules lack steric hindrance protection, have high α-hydrogen activity, and are prone to reduction cracking during charge and discharge, triggering gas generation side reactions in the cell; at the same time, the solvent molecules have an excessively strong solvation effect on sodium ions, which easily leads to oxidative decomposition at the layered oxide cathode interface under high voltage conditions, causing damage to the cathode CEI film and dissolution of transition metals; in addition, conventional ether systems are difficult to control the uniformity of sodium ion deposition, which easily induces sodium dendrite growth, punctures the separator, and causes micro-short circuits in the battery. Especially under high-temperature cycling conditions, there are problems such as easy dissolution of the SEI film, aggravated interfacial side reactions, and rapid capacity decay, which seriously restrict the high-temperature stability and long cycle life of anode-less sodium-ion batteries.

[0004] In existing technologies, some studies have applied simple borohydride salts to modify sodium-ion battery electrolytes in an attempt to improve the interface performance of the negative electrode. However, the commonly used sodium borohydride (NaBH4) has a simple open-chain borohydride structure with poor electron delocalization of the molecular skeleton and weak oxidation stability. It is prone to decomposition and failure under high-voltage positive electrode conditions and cannot be adapted to the 4.0V high-voltage positive electrode system. At the same time, this type of borohydride salt has extremely low solubility in traditional ether solvents and is prone to precipitation. It not only fails to play a role in interface regulation but also deteriorates the ion conduction performance of the electrolyte, making it difficult to meet the interface modification requirements of both the positive and negative electrodes.

[0005] In summary, existing ether-based electrolytes for anode-free sodium-ion batteries generally suffer from technical defects such as low solubility of boron-hydrogen additives, poor solvent molecule stability, severe gas generation at high temperatures, insufficient stability of the SEI / CEI interface film, easy formation of sodium dendrites, and severe degradation during high-voltage and high-temperature cycling. These defects make it difficult to simultaneously meet the requirements of anode-free sodium-ion batteries for high-temperature interface stability, long cycle life, and wide temperature range adaptability. Summary of the Invention

[0006] To address the aforementioned deficiencies, the first objective of this application is to provide an electrolyte for a negative electrode-free sodium-ion battery that can reduce high-temperature SEI dissolution, suppress high-temperature gas generation and sodium dendrite growth, and improve high-temperature interface stability and overall battery cycle performance.

[0007] To achieve the above-mentioned objectives, this application adopts the following technical solution: A high-temperature electrolyte for a negative electrode-free sodium-ion battery comprises a sodium salt, an additive, and a solvent, wherein the solvent comprises at least an asymmetric branched ether and a pyrrolidine-based ionic liquid, and the additive is Na₂B. 12 H 12 Sodium salt, additives and solvent are mixed to obtain an electrolyte for use in a negative electrode-less sodium-ion battery.

[0008] The mechanism of action of this application is as follows: This application discloses a high-temperature electrolyte for a negative electrode-free sodium-ion battery, employing an asymmetric branched-chain ether-pyrrolidine ionic liquid composite solvent system, combined with a closed-cell type sodium dodecyl hydrogen dodecoborate (Na2B). 12 H 12 As an additive, it can effectively increase the content of non-polar components in the electrolyte-electrode interface, reduce high-temperature SEI dissolution, inhibit high-temperature gas generation and sodium dendrite growth, and improve high-temperature interface stability and overall battery cycle performance.

[0009] (1) Selection of additives Conventional borohydride modified electrolytes mostly use ordinary borohydride salts, which lack a highly stable closed cage structure, have a narrow electrochemical window and poor voltage resistance, making them unsuitable for high-voltage negative electrode-free battery systems. Furthermore, they lack ionic liquid synergistic solubilization systems, resulting in extremely low utilization of borohydride additives and very limited modification effects.

[0010] This application employs a closed-cell boron-hydrogen functional component (Na2B). 12 H 12 As an additive: Na2B 12 H 12 The anion is a closed cage-type B. 12 H 12 2-The cage-like framework electrons are highly delocalized, exhibiting superior oxidation and reduction stability compared to simple borohydrides such as NaBH4; Na2B 12 H 12 It can achieve dual-sided interface control of positive and negative electrodes: On the one hand, the closed boron-hydrogen cage anion has a high oxidation potential and preferentially undergoes partial oxidation and decomposition on the positive electrode surface to form a dense CEI passivation film containing boron inorganic components, which blocks the continuous oxidation and decomposition of solvent molecules at the positive electrode interface, inhibits the dissolution of transition metals, and broadens the electrochemical stability window of the electrolyte; on the other hand, a small amount of boron-hydrogen cage fragments are reduced on the surface of the sodium negative electrode current collector to participate in the construction of the SEI film, optimize the sodium deposition morphology, inhibit the growth of sodium dendrite nucleation, and at the same time, do not cause a significant increase in interfacial impedance.

[0011] (2) Compound solvent system Using closed-cage borohydride functional components can solve the problems existing in existing borohydride salts. However, neither existing single ether solvent systems nor conventional compound solvent systems can solve the dissolution problem of closed-cage borohydride functional components, which leads to additive precipitation and failure of interface modification. Conventional compound solvent systems cannot achieve weak solvation effect and α-hydrogen protection, making it difficult to suppress solvent side reactions and high-temperature gas generation at the molecular level.

[0012] To this end, this application developed a composite solvent system of "asymmetric branched ether + pyrrolidine ionic liquid" for use with closed-cage boron-hydrogen functional components (Na2B). 12 H 12 ), where: ionic liquids are used to improve Na2B 12 H 12 In terms of solubility in ether solvents, ionic liquids are diluted with a large amount of asymmetric branched ethers using a small volume percentage, ensuring that the electrolyte as a whole has low viscosity and high ionic conductivity.

[0013] Asymmetric branched ether molecules possess a unique substitution structure: the A-terminus retains a methoxy functional group, and the α-hydrogen atom on the carbon atom bonded to the methoxy group is replaced by an alkyl group (R2); an alkyl group (R1) is introduced at the B-terminus to provide steric hindrance and achieve a weak solvation effect. Each oxygen atom in the ether molecule has a methoxy or methylene group on one side, maintaining a moderate coordination ability to sodium ions and ensuring the degree of dissociation of the sodium salt; the other side is connected to a highly hindered alkyl group, achieving a weak solvation effect. This not only enhances the ether solvent's own antioxidant capacity and reduction stability but also protects the α-hydrogen, reducing the risk of reductive cracking of the α-hydrogen.

[0014] The compound solvent system employs multiple synergistic mechanisms: ionic liquids address the insufficient solubility of sodium borohydride cages; asymmetric branched ethers, relying on their unique molecular structure, reshape the sodium ion solvation sheath, weakening the reactivity of solvent molecules and reducing solvent side reactions; and borohydride cage anions construct stable positive and negative electrode interface films. Under the synergistic effect of these multiple mechanisms, high-temperature SEI film dissolution is reduced, alleviating cell gas generation issues, effectively suppressing sodium dendrite growth in negative electrode-less sodium-ion batteries, reducing interface side reactions, and significantly improving the battery's high-temperature cycle life and interface stability.

[0015] Further settings include: Based on the total mass of the electrolyte, the additive Na2B 12 H 12 The mass percentage content is 0.1%-3%.

[0016] The sodium salt is selected from at least one of NaPF6, NaClO4, NaBF4, NaAsF6, NaODFB, NaCF3SO3, Na(CF3SO2)3, Na(CF3CO2)2N, Na(CF3SO2)2N, and Na(SO2C2F5)2N.

[0017] The concentration of sodium salt in the electrolyte is 0.4–2 mol / L, preferably 0.8–1 mol / L.

[0018] The structural formula of the asymmetric branched ether is as follows: ; In the formula: n = 1-6; R1 is a straight-chain or branched alkyl group with 2 to 6 carbon atoms, and R2 is a straight-chain or branched alkyl group with 1 to 6 carbon atoms.

[0019] The pyrrolidine ionic liquid is selected from at least one of 1-methyl-1-propylpyrrolidine bis(fluorosulfonyl)imide, N-methyl, butylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, 1-methyl-1-propylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, and 1-butyl-1-methylpyrrolidine bis(fluorosulfonyl)imide.

[0020] The volume percentage of the ionic liquid in the solvent is 3%-10%, preferably 3%-6%.

[0021] The second aspect of this application aims to provide a method for preparing a high-temperature electrolyte for a negative electrode-free sodium-ion battery, comprising the following steps: dissolving sodium salt in a mixed solvent of asymmetric branched ether and pyrrolidine ionic liquid in an argon atmosphere glove box with a water content of <10ppm, stirring until completely dissolved; and finally adding the additive Na2B. 12 H 12 Stir thoroughly to completely dissolve, and obtain a high-temperature electrolyte for use in a negative electrode-free sodium-ion battery.

[0022] The third objective of this application is to provide an application of a high-temperature electrolyte for a non-polar sodium-ion battery in a non-polar sodium-ion battery.

[0023] The negative electrode-free sodium-ion battery includes a positive electrode, a negative electrode current collector, an electrolyte, and a separator.

[0024] The electrolyte is the aforementioned high-temperature electrolyte used in negative electrode-free sodium-ion batteries.

[0025] The positive electrode sheet includes a positive current collector and a positive active material adhered to the positive current collector. The positive active material is selected from any one of sodium layered transition metal oxides, polyanionic materials, Prussian blue, and iron sulfide.

[0026] The diaphragm is selected from any one of polyethylene monolayer membrane (PE), polypropylene monolayer membrane (PP), multilayer microporous membrane composed of PP and PE, cellulose nonwoven fabric, polyvinylidene fluoride porous membrane, polyimide electrospun porous membrane, and glass fiber diaphragm, preferably glass fiber diaphragm.

[0027] The negative electrode current collector is made of aluminum foil or copper foil, and a conductive coating is coated on the surface of the negative electrode current collector. The conductive coating is a carbon-based conductive layer, which is at least one of graphene, carbon nanotubes or hard carbon, and the coating thickness is 1 to 5 μm.

[0028] Compared with existing technical solutions, this application has the following advantages: (1) A high-temperature electrolyte for a negative electrode-free sodium-ion battery of this application adopts an asymmetric branched ether-pyrrolidine ionic liquid composite solvent system, combined with closed cage-type sodium dodecyl hydrogen dodecoborate (Na2B) 12 H 12 As an additive, closed-cage type B 12 H 12 2- The anionic skeleton electrons are highly delocalized, exhibiting excellent oxidation and reduction stability compared to simple borohydrides such as NaBH4. The ionic liquid improves the solubility of the additive in ether solvents, while the asymmetric branched ether achieves a weak solvation effect and protects the α-hydrogen of the ether through its special molecular substitution structure. These three factors synergistically regulate the sodium ion solvation sheath layer. At the same time, a stable boron-containing inorganic passivation film is constructed at the positive and negative electrode interfaces, improving the electrode-electrolyte interface characteristics and widening the electrochemical window of the electrolyte. This fundamentally alleviates the technical challenges of high-temperature SEI film dissolution, high-temperature gas generation, sodium dendrite growth, and intensified interfacial side reactions under high voltage in anode-less sodium-ion batteries.

[0029] This application enables uniform and stable sodium deposition and stripping behavior: asymmetric branched ethers reshape the sodium ion solvation structure through steric hindrance, reducing the reactivity of solvent molecules; Na2B 12 H 12 A stable CEI / SEI passivation film is preferentially generated at the electrode interface, resulting in a uniform interface charge distribution. This effectively inhibits the growth of sodium dendrites, significantly reduces the risk of internal short circuits in the electrodeless battery, and improves the battery's operational safety and lifespan.

[0030] (2) The electrolyte of this application, when applied to a negative electrode-less sodium-ion battery, has the following excellent properties: This application's anode-free sodium-ion battery exhibits excellent long-term cycling stability at room temperature and high temperature: When paired with NFPP cathode material, at 25℃, after 1000 cycles at a 0.5C / 1C rate, the battery capacity retention is greater than 80%; at 45℃, after 500 cycles at a 0.5C / 1C rate, the battery capacity retention is greater than 80%, significantly suppressing electrolyte decomposition and interfacial film damage at high temperatures, demonstrating outstanding high-temperature tolerance. When paired with NFM cathode material, at a 4.0V cutoff voltage and 25℃, after 500 cycles at a 0.5C / 1C rate, the battery capacity retention is greater than 80%, and the coulombic efficiency remains stable under long-term cycling at room temperature, without significant capacity drop or rapid decay.

[0031] The electrolyte formulation of this application is simple and controllable, with a low proportion of ionic liquid addition, balancing low viscosity and high conductivity of the electrolyte. The sodium salt, solvent and additive raw materials used are highly versatile and have good compatibility with mainstream sodium battery cathode materials such as NFPP and NFM, which facilitates actual battery cell production and has good prospects for industrial application. Detailed Implementation

[0032] The technical solutions of this application will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of this application, and should not be construed as limiting the scope of protection of this application. All technologies implemented based on the above content of this application are covered within the scope of protection intended by this application.

[0033] Unless otherwise stated, the raw materials and reagents used in the following examples are all commercially available products or can be prepared by known methods; the electrolytes were all prepared in an argon atmosphere glove box with a water content of <10ppm; the batteries were all negative electrode-free sodium-ion batteries, and the negative electrode current collector was a copper foil with a 2μm carbon-based conductive layer on its surface; NFPP, NFM positive electrodes and glass fiber separators were used for assembly and testing respectively.

[0034] Example 1

[0035] A high-temperature electrolyte for use in a negative electrode-free sodium-ion battery, the electrolyte comprising sodium salt, additives and solvent.

[0036] Solvent: The asymmetric branched ether is 1-ethoxy-2-methoxypropane, and the ionic liquid is N-methyl, butylpyrrolidine bis(trifluoromethanesulfonyl)imide salt; the volume percentage of the ionic liquid in the solvent is 6%.

[0037] Sodium salt: Composed of sodium hexafluorophosphate and sodium bis(trifluoromethanesulfonyl)imide, with a total sodium salt concentration of 1.0 mol / L, of which: sodium hexafluorophosphate (NaPF6) 0.6 mol / L; sodium bis(trifluoromethanesulfonyl)imide (NaTFSI) 0.4 mol / L.

[0038] Additive: Na2B 12 H 12 It accounts for 1.0% of the total mass of the electrolyte.

[0039] Preparation method: Prepare sodium salt and Na2B according to the above formula. 12 H 12 Solvent; In an argon atmosphere glove box with a water content <10ppm, dissolve the thoroughly dried sodium salt in a mixed solvent of 1-ethoxy-2-methoxypropane and N-methyl, butylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, stirring until completely dissolved; finally, add additive Na2B. 12 H 12 Stir thoroughly to completely dissolve, and obtain a high-temperature electrolyte for use in a negative electrode-free sodium-ion battery.

[0040] To investigate the effects of different asymmetric branched ethers on electrolyte performance, experiments were conducted in Examples 2 and 3.

[0041] Example 2

[0042] The preparation method is the same as in Example 1, except that the solvent is prepared as follows: Solvent: The asymmetric branched ether is 1-n-propoxy-2-methoxypropane; the ionic liquid is N-methyl, butylpyrrolidine bis(trifluoromethanesulfonyl)imide salt; the volume percentage of the ionic liquid in the solvent is 6%.

[0043] Example 3

[0044] The preparation method is the same as in Example 1, except that the solvent is prepared as follows: Solvent: The asymmetric branched ether is 1-isopropoxy-2-methoxypropane; the ionic liquid is N-methyl, butylpyrrolidine bis(trifluoromethanesulfonyl)imide salt; the volume percentage of the ionic liquid in the solvent is 6%.

[0045] To investigate the effects of different ionic liquids on electrolyte performance, experiments in Examples 4 and 5 were conducted.

[0046] Example 4

[0047] The preparation method is the same as in Example 1, except that the solvent is prepared as follows: Solvent: The asymmetric branched ether is 1-ethoxy-2-methoxypropane; the ionic liquid is 1-methyl-1-propylpyrrolidine bis(trifluoromethanesulfonyl)imine salt; the volume percentage of the ionic liquid in the solvent is 6%.

[0048] Example 5

[0049] The preparation method is the same as in Example 1, except that the solvent is prepared as follows: Solvent: The asymmetric branched ether is 1-ethoxy-2-methoxypropane; the ionic liquid is 1-methyl-1-propylpyrrolidineonium bis(fluorosulfonyl)imide; the volume percentage of the ionic liquid in the solvent is 6%.

[0050] To investigate Na2B 12 H 12 The effect of dosage on electrolyte performance was investigated in Examples 6 and 7.

[0051] Example 6

[0052] The preparation method is the same as in Example 1, except that the Na2B is adjusted. 12 H 12 The amount added.

[0053] Additive: Na2B 12 H 12 It accounts for 0.1% of the total mass of the electrolyte.

[0054] Example 7

[0055] The preparation method is the same as in Example 1, except that the Na2B is adjusted. 12 H 12 The amount added.

[0056] Additive: Na2B 12 H 12 It accounts for 3.0% of the total mass of the electrolyte.

[0057] To investigate the effect of the amount of ionic liquid on the performance of the electrolyte, experiments were conducted in Examples 8 and 9.

[0058] Example 8

[0059] The preparation method is the same as in Example 1, except that the amount of ionic liquid in the solvent is adjusted.

[0060] Solvent: The asymmetric branched ether is 1-ethoxy-2-methoxypropane; the ionic liquid is N-methyl, butylpyrrolidine bis(trifluoromethanesulfonyl)imide salt; the volume percentage of the ionic liquid in the solvent is 3%.

[0061] Example 9

[0062] The preparation method is the same as in Example 1, except that the amount of ionic liquid in the solvent is adjusted.

[0063] Solvent: The asymmetric branched ether is 1-ethoxy-2-methoxypropane; the ionic liquid is N-methyl, butylpyrrolidine bis(trifluoromethanesulfonyl)imide salt; the volume percentage of the ionic liquid in the solvent is 10%.

[0064] To investigate the effect of sodium salt concentration on electrolyte performance, experiments in Examples 10 and 11 were conducted.

[0065] Example 10

[0066] The preparation method is the same as in Example 1, except that the total concentration of sodium salt is adjusted to 0.4 mol / L.

[0067] Sodium salts: Sodium hexafluorophosphate (NaPF6): 0.2 mol / L; Sodium bis(trifluoromethanesulfonyl)imide (NaTFSI): 0.2 mol / L, total sodium salt concentration 0.4 mol / L.

[0068] Example 11

[0069] The preparation method is the same as in Example 1, except that the total concentration of sodium salt is adjusted to 2.0 mol / L.

[0070] Sodium salts: Sodium hexafluorophosphate (NaPF6): 1.2 mol / L; Sodium bis(trifluoromethanesulfonyl)imide (NaTFSI): 0.8 mol / L, total sodium salt concentration 2.0 mol / L.

[0071] Comparative Example 1 The preparation method is the same as in Example 1, except that the asymmetric branched ether is replaced with a conventional chain ether in the solvent.

[0072] Solvent: Diethylene glycol dimethyl ether (G2) is used for conventional chain ethers; N-methyl, butylpyrrolidine bis(trifluoromethanesulfonyl)imide salt is used for ionic liquids; the volume percentage of ionic liquids in the solvent is 6%.

[0073] Comparative Example 2 The preparation method is the same as in Example 1, except that only asymmetric branched ethers are used in the solvent, and no ionic liquids are added.

[0074] Solvent: 1-ethoxy-2-methoxypropane.

[0075] Comparative Example 3 The preparation method is the same as in Example 1, except that the additive Na2B is used. 12 H 12 Replace with NaBH4.

[0076] Additive: NaBH4, accounting for 1.0% of the total mass of the electrolyte.

[0077] Comparative Example 4 The preparation method is the same as in Example 1, except that the additive Na2B is used. 12 H 12 Replace with Na2B 10 H 10 .

[0078] Additive: Na2B 10 H 10 It accounts for 1.0% of the total mass of the electrolyte.

[0079] Comparative Example 5 The preparation method is the same as in Example 1, except that Na2B is not added to the electrolyte. 12 H 12 The electrolyte composition is as follows: Solvent: The asymmetric branched ether is 1-ethoxy-2-methoxypropane, and the ionic liquid is N-methyl, butylpyrrolidine bis(trifluoromethanesulfonyl)imide salt; the volume percentage of the ionic liquid in the solvent is 6%.

[0080] Sodium salt: Composed of sodium hexafluorophosphate and sodium bis(trifluoromethanesulfonyl)imide, with a total sodium salt concentration of 1.0 mol / L, of which: sodium hexafluorophosphate (NaPF6), 0.6 mol / L; sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), 0.4 mol / L.

[0081] Application Examples

[0082] The electrolytes prepared in the aforementioned examples and comparative examples were used in non-negative electrode sodium-ion batteries (NFPP batteries and NFM batteries) to test their electrochemical performance.

[0083] A negative electrode-free sodium-ion battery includes a positive electrode, a negative electrode current collector, a separator, and an electrolyte.

[0084] Positive electrode preparation: The positive electrode active material is selected from NFPP (Na4Fe3(PO4)2P2O7) or NFM (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2), positive electrode active material, conductive carbon black (SP), and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 92:5:3, and an appropriate amount of N-methylpyrrolidone (NMP) is added and stirred thoroughly until the slurry is uniform; the mixed slurry is uniformly coated on the surface of aluminum foil current collector, and then dried, rolled and compacted, and cut into sheets to obtain NFPP positive electrode sheets and NFM positive electrode sheets respectively.

[0085] Negative electrode current collector: Copper foil with a 2μm carbon-based conductive layer on its surface is used as the negative electrode current collector.

[0086] Separator: Glass fiber diaphragm is selected.

[0087] Electrolyte: The electrolyte prepared in the aforementioned examples and comparative examples is used.

[0088] Battery assembly process: The positive electrode sheet, separator, and negative electrode current collector are stacked and aligned in sequence to obtain a bare cell; the bare cell is packaged in an aluminum-plastic film packaging bag to complete the dry cell preparation, and then the electrolyte is injected into the dry cell to complete the heat sealing; after going through the electrolyte full wetting, small current activation formation, and cell shaping processes in sequence, a negative electrode-free sodium-ion battery is finally obtained.

[0089] Performance testing: The Blue Battery Testing System was used, and the test environment temperature was set to 25℃ normal temperature environment and 45℃ high temperature environment according to the experimental requirements. Corresponding voltage ranges were matched for different cathode materials, with the voltage range of NFPP battery being 2.0 V-3.6 V and the voltage range of NFM battery being 2.0 V-4.0 V.

[0090] (1) NFPP battery room temperature long cycle performance test (25 ℃, 2.0 V-3.6 V) At room temperature of 25℃, the NFPP system sodium-ion battery without negative electrode was charged to 3.6 V with a constant current of 0.1 C and then discharged to 2.0 V with a constant current of 0.1 C. This charge-discharge cycle was repeated twice to complete the cell activation. After activation, the battery was continuously cycled for 1000 times using a charge-discharge regime of 0.5 C to 3.6 V and 1 C to 2.0 V. The discharge capacity during the cycle was recorded, and the battery capacity retention rate after 1000 cycles was calculated.

[0091] (2) High-temperature cycle performance test of NFPP battery (45 ℃, 2.0 V-3.6 V) Under high temperature conditions of 45℃, the NFPP system sodium-ion battery without negative electrode was charged to 3.6 V with a constant current of 0.1 C and then discharged to 2.0 V with a constant current of 0.1 C. The charge-discharge cycle was repeated twice to complete the cell activation. After activation, the battery was continuously cycled for 500 times using a charge-discharge regime of 0.5 C constant current to 3.6 V and 1 C constant current to 2.0 V. The discharge capacity during the cycle was recorded, and the battery capacity retention rate after 500 cycles was calculated.

[0092] (3) Room temperature cycle performance test of NFM battery (25 ℃, 2.0 V-4.0 V) At room temperature of 25℃, the NFM system sodium-ion battery without negative electrode was charged to 4.0 V with a constant current of 0.1 C and then discharged to 2.0 V with a constant current of 0.1 C. This charge-discharge cycle was repeated twice to complete the cell activation. After activation, the battery was continuously cycled for 500 times using a charge-discharge regime of 0.5 C to 4.0 V and 1 C to 2.0 V. The discharge capacity during the cycle was recorded, and the battery capacity retention rate after 500 cycles was calculated.

[0093] The formula for calculating battery capacity retention rate is as follows: Capacity retention rate = Discharge capacity for the corresponding number of cycles / First stable cycle discharge capacity after activation × 100%.

[0094] (4) NFM battery internal resistance test DC pulse internal resistance tests were performed on NFM sodium-ion batteries at 25 ℃ and 50% SOC. The batteries were allowed to stand until the open-circuit voltage stabilized, and a 1C constant current discharge pulse was applied for 10 s. The open-circuit voltage before the pulse and the terminal voltage at the end of the pulse were collected. The DC internal resistance was calculated based on the voltage difference and the pulse current.

[0095] The test results are shown in Table 1.

[0096] Table 1 .

[0097] As shown in Table 1, the test results indicate that: (1) The sodium-ion batteries without negative electrodes prepared in Examples 1-11 of this application have significantly better capacity retention rates in room temperature long cycle, high temperature cycle and room temperature cycle of the NFPP positive electrode system and the NFM positive electrode system than the respective comparative examples. They also have lower battery internal resistance, which fully verifies the excellent electrochemical performance of the electrolyte technology solution of this application.

[0098] In Comparative Example 1, the electrolyte used conventional chain ether diethylene glycol dimethyl ether (G2) instead of the asymmetric branched ether solvent of the present invention. It could not effectively reshape the sodium ion solvated sheath, the solvent reduction and decomposition were aggravated, the uniformity of sodium deposition was worsened, and the capacity retention rate of NFPP after 1000 cycles at -25℃ was only 62.4%. The capacity decay was further aggravated under high temperature conditions, and all performance was significantly worse than that of the Example.

[0099] Comparative Example 2: No ionic liquid was added to the electrolyte. Only an asymmetric branched ether solvent was used. The borohydride additive could not be completely dissolved and precipitated as a solid. The electrolyte system was unbalanced, making it difficult to construct a stable SEI passivation film. The ability to suppress sodium dendrites was greatly weakened, making it the group with the worst cycle performance among all samples in this group.

[0100] The two sets of comparative examples above demonstrate that the asymmetric branched ether solvent and pyrrolidine ionic liquid complex system is an essential technical feature of the scheme in this application.

[0101] Comparative Example 3 replaced the additive with NaBH4. This substance lacks a cage-like borohydride stable structure. The active hydrogen of BH is prone to side reactions that cause cell gas generation. The interfacial film stability is poor. The capacity retention rate of NFPP after 1000 cycles at -25℃ is only 68.9%, and the cycle performance is significantly lower than that of the example.

[0102] Comparative Example 4 uses a closed-cell type borohydride Na2B 10 H 10 As an additive, the cage size is poorly matched with sodium ions, resulting in weak interfacial adsorption and film formation capabilities. It cannot achieve efficient dual-sided interface control of the positive and negative electrodes, and its performance is lower than that of the embodiments in this application.

[0103] Comparative Example 5: Electrolyte without added Na2B 12 H 12 Cage-type borohydride additives lack interface modification components, making it impossible to form a dense and stable passivation film on the current collector surface. Sodium dendrite growth is severe, and side reactions continuously consume electrolyte, resulting in a significant increase in battery internal resistance and a substantial decline in cycle performance. The capacity retention rate of NFPP after 1000 cycles at -25℃ is only 60.8%.

[0104] (2) By adjusting the type of branched ether solvent, the type and volume ratio of ionic liquid, the amount of cage-type borohydride additive, and the total concentration of sodium salt in the electrolyte, the room temperature and high temperature cycling electrochemical performance and battery internal resistance of the negative electrode-free sodium-ion battery can be effectively controlled.

[0105] Comparing Examples 1-3, it can be seen that, under the condition that other conditions remain the same, using asymmetric branched ether solvents with different structures can achieve a cycle capacity retention rate of more than 80% for both NFPP and NFM cathode systems; among them, Example 1 has the best overall cycle performance and internal resistance level.

[0106] Comparing Examples 1 and 4-5, it can be seen that pyrrolidine ionic liquids can improve the electrolyte's solubility and oxidation stability. Compared with pyrrolidine-onium bis(fluorosulfonyl)imide ionic liquids, pyrrolidine-onium bis(fluorosulfonyl)imide ionic liquids exhibit better overall battery performance when combined with asymmetric branched ethers, making them the preferred ionic liquid components for this application.

[0107] Comparing Examples 1 and 6-7, it can be seen that when the amount of additive is within the range of 0.1% to 3.0% by mass, the cage-type borohydride additive can maintain the cycle capacity retention rate of both NFPP and NFM systems above 80%. If the addition amount is too low (0.1%), the supply of interface modification components is insufficient, the SEI film density is insufficient, and the performance decreases slightly. When the addition amount is 3.0%, the electrolyte viscosity increases slightly, and the performance decreases slightly. Under the condition of 1.0% addition amount, the film formation effect and electrolyte ion conduction capacity are balanced, and the overall performance is optimal.

[0108] Comparing Examples 1 and 8-9, it can be seen that: as a control experiment on the volume fraction of ionic liquid, an ionic liquid volume fraction of 3% to 10% can improve the electrolyte system; when the ionic liquid fraction is 6%, it ensures that the borohydride additive is fully dissolved without causing the electrolyte viscosity to be too high, resulting in the optimal battery cycle performance; if the fraction is too low, the additive will not be completely dissolved, and if the fraction is too high, the system viscosity will increase and the battery internal resistance will rise.

[0109] Comparing Examples 1 and 10-11, it can be seen that: as a control experiment with a variable total sodium salt concentration, the battery can operate normally and maintain a cycle capacity retention rate of more than 80% when the total sodium salt concentration is in the range of 0.4 mol / L to 2.0 mol / L; if the total concentration is too low, the sodium salt dissociation is insufficient and the ionic conductivity decreases; if the total concentration is too high, the electrolyte viscosity increases and ion migration is hindered; the battery has the best overall performance in the 1.0 mol / L concentration range.

[0110] Summarize: This application presents a high-temperature electrolyte for use in a cathodeless sodium-ion battery. When applied to a cathodeless sodium-ion battery, the following characteristics are observed: the NFPP cathode maintains a capacity retention of up to 86.8% after 1000 cycles at 25°C and 2.0-3.6 V using 0.5C / 1C; the NFPP cathode maintains a capacity retention of up to 84.6% after 500 cycles at 45°C and 2.0-3.6 V using 0.5C / 1C; and the NFM cathode maintains a capacity retention of up to 85.4% after 500 cycles at 4.0 V cutoff voltage, 25°C, and 2.0-4.0 V using 0.5C / 1C. The electrolyte exhibits stable coulombic efficiency under long-term cycling at room temperature, with no significant capacity drop or rapid decay, and effectively reduces the battery's internal resistance. It can significantly suppress electrolyte decomposition and interfacial film failure under high temperature conditions, inhibit sodium dendrite growth, improve the stability of the current collector-electrolyte interface, and meet the needs of sodium-ion batteries without negative electrodes for use in both room temperature and high temperature conditions, thus possessing extremely high industrialization and promotion value.

Claims

1. A high-temperature electrolyte for a negative electrode-less sodium-ion battery, characterized in that: The mixture includes a sodium salt, an additive, and a solvent, wherein the solvent comprises at least an asymmetric branched ether or a pyrrolidine ionic liquid, and the additive is Na₂B. 12 H 12 Sodium salt, additives and solvent are mixed to obtain an electrolyte for use in a negative electrode-free sodium-ion battery. The structural formula of the asymmetric branched ether is as follows: ; In the formula: n = 1-6; R1 is a straight-chain or branched alkyl group with 2 to 6 carbon atoms, and R2 is a straight-chain or branched alkyl group with 1 to 6 carbon atoms.

2. The high-temperature electrolyte for a negative electrode-less sodium-ion battery according to claim 1, characterized in that: Based on the total mass of the electrolyte, the additive Na2B 12 H 12 The mass percentage content is 0.1%-3%.

3. The high-temperature electrolyte for a negative electrode-less sodium-ion battery according to claim 1, characterized in that: The sodium salt is selected from at least one of NaPF6, NaClO4, NaBF4, NaAsF6, NaODFB, NaCF3SO3, Na(CF3SO2)3, Na(CF3CO2)2N, Na(CF3SO2)2N, and Na(SO2C2F5)2N.

4. The high-temperature electrolyte for a negative electrode-less sodium-ion battery according to claim 1, characterized in that: The concentration of sodium salt in the electrolyte is 0.4–2 mol / L.

5. The high-temperature electrolyte for a negative electrode-less sodium-ion battery according to claim 1, characterized in that: The pyrrolidine ionic liquid is selected from at least one of 1-methyl-1-propylpyrrolidine bis(fluorosulfonyl)imide, N-methyl, butylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, 1-methyl-1-propylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, and 1-butyl-1-methylpyrrolidine bis(fluorosulfonyl)imide.

6. The high-temperature electrolyte for a negative electrode-less sodium-ion battery according to claim 1, characterized in that: The volume percentage of the ionic liquid in the solvent is 3%-10%.

7. A method for preparing the high-temperature electrolyte for a negative electrode-free sodium-ion battery as described in claim 1, characterized in that: Includes the following steps: In an argon atmosphere glove box with a water content of <10 ppm, the sodium salt was dissolved in a mixed solvent of asymmetric branched ether and pyrrolidine ionic liquid, and stirred until completely dissolved; finally, the additive Na2B was added. 12 H 12 Stir thoroughly to completely dissolve, and obtain a high-temperature electrolyte for use in a negative electrode-free sodium-ion battery.

8. The application of the high-temperature electrolyte of claim 1 for a negative electrode-free sodium-ion battery in the preparation of a negative electrode-free sodium-ion battery.